2017
DOI: 10.1590/1980-5373-mr-2017-0801
|View full text |Cite
|
Sign up to set email alerts
|

Electrical, Thermal and Mechanical Properties of Epoxy/CNT/Calcium Carbonate Nanocomposites

Abstract: Epoxy/CNT and epoxy/CNT/calcium carbonate nanocomposites were produced via in situ polymerization assisted by ultrasonication without solvent and electrical, mechanical, thermal and thermomechanical properties of nanocomposites were evaluated. Epoxy/CNT presented very low percolation threshold, near 0.05 wt % and nanocomposites with higher contents of CNT presented further increase in electrical conductivity. The addition of calcium carbonate in epoxy/CNT nanocomposites increased the electrical conductivity, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The data for AC conductivity measurements observed over a wide frequency range are comparable to the admittance and conductivity measurements published for SWNTs [20] which showed an increase in admittance for a 0.025 wt% sample. Data presented by Backes et al for an epoxy resin (Araldite LY1316 with Aradur HY1208 hardener) and MWCNT composite show an increase in electrical conductivity (decrease in resistivity) as frequency is increased for a 0.05 wt% CNT sample, a smaller increase in conductivity for a 0.1 wt% sample, and essentially no change for a 0.2 wt% and 0.3 wt% sample [28]. Similar work by Sandler et al with epoxy resin (Araldite LY556 with Araldite HY932 hardener) and MWCNTs showed increasing conductivity with increasing frequency for 0.001 wt% and 0.0025 wt% samples, however, 0.005 wt% samples and higher CNT concentrations exhibited nearly linear conductivity values up to a frequency of 100 kHz [21].…”
Section: Impact Of Temperature On Composites Resistivitymentioning
confidence: 97%
“…The data for AC conductivity measurements observed over a wide frequency range are comparable to the admittance and conductivity measurements published for SWNTs [20] which showed an increase in admittance for a 0.025 wt% sample. Data presented by Backes et al for an epoxy resin (Araldite LY1316 with Aradur HY1208 hardener) and MWCNT composite show an increase in electrical conductivity (decrease in resistivity) as frequency is increased for a 0.05 wt% CNT sample, a smaller increase in conductivity for a 0.1 wt% sample, and essentially no change for a 0.2 wt% and 0.3 wt% sample [28]. Similar work by Sandler et al with epoxy resin (Araldite LY556 with Araldite HY932 hardener) and MWCNTs showed increasing conductivity with increasing frequency for 0.001 wt% and 0.0025 wt% samples, however, 0.005 wt% samples and higher CNT concentrations exhibited nearly linear conductivity values up to a frequency of 100 kHz [21].…”
Section: Impact Of Temperature On Composites Resistivitymentioning
confidence: 97%
“…The resistivity of CTS biopolymer is very high being equivalent to 10 5 ohm-m. Hu et al [49] showed that the resistivity of chitosan-reinforced Ti3C2X films was increased gradually with the increase of CTS. Even dispersing small amounts of CNTs into insulating polymers can effectively reduce the electrical resistivity of polymeric matrices [50]. The frequencydependent resistivity (ρ) was measured at room temperature for the CTS/1%f-MWCNTs, CTS/3%f-MWCNTs, and CTS/5%f-MWCNTs composites sintered at 150 • C for 1 h in an oven in the form of sheets about 0.5 to 1.0 mm thick.…”
Section: Analysis Of Electrical Propertiesmentioning
confidence: 99%
“…Electrically conductive polymer materials have been proven to be used in fuel cells like printed circuit boards, electronic devices, anti-static electricity, electromagnetic shielding, etc (Backes et al, 2017;Md Saleh et al, 2020). However, there are little numbers of inherently conductive polymers commercially available in the market today (Jin and Park, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) are normally produced from concentrically-rolled graphene sheets that have asymmetric helicity (Backes et al, 2017). The SP 2 of the carbon atoms of the CNTs provide high thermal conductivity as well as excellent high electronic and chemical stability (Md Saleh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%